A Randomized Trial of Social Comparison Feedback and Financial Incentives to Increase Physical Activity. Issue 6 (July 2016) - Patel, Mitesh S.; Volpp, Kevin G.; Rosin, Roy; Bellamy, Scarlett L.; Small, Dylan S.; Fletcher, Michele A.; Osman-Koss, Rosemary; Brady, Jennifer L.; Haff, Nancy; Lee, Samantha M.; Wesby, Lisa; Hoffer, Karen; et al.
Purpose: To compare the effectiveness of different combinations of social comparison feedback and financial incentives to increase physical activity. Design: Randomized trial (Clinicaltrials.gov number, NCT02030080). Setting: Philadelphia, Pennsylvania. Participants: Two hundred eighty-six adults. Interventions: Twenty-six weeks of weekly feedback on team performance compared to the 50th percentile (n = 100) or the 75th percentile (n = 64) and 13 weeks of weekly lottery-based financial incentive plus feedback on team performance compared to the 50th percentile (n = 80) or the 75th percentile (n = 44) followed by 13 weeks of only performance feedback. Measures: Mean proportion of participant-days achieving the 7000-step goal during the 13-week intervention. Analysis: Generalized linear mixed models adjusting for repeated measures and clustering by team. Results: Compared to the 75th percentile without incentives during the intervention period, the mean proportion achieving the 7000-step goal was significantly greater for the 50th percentile with incentives group (0.45 vs 0.27, difference: 0.18, 95% confidence interval [CI]: 0.04 to 0.32; P = .012) but not for the 75th percentile with incentives group (0.38 vs 0.27, difference: 0.11, 95% CI: −0.05 to 0.27; P = .19) or the 50th percentile without incentives group (0.30 vs 0.27, difference: 0.03, 95% CI: −0.10 to 0.16; P = .67). Conclusion: Social comparison to the 50th percentile with financial incentives was most effective for increasing physical activity.